Synthesis and luminescence spectroscopy of YNbO4 doped with Eu(III) - Massabni, A.m.g. [UNESP]; Montandon, G.j.m. [UNESP]; Santos, M.a. Couto Dos [UNESP] (ABM, ABC, ABPol, 1998)
The solid compound YNbO4:Eu3+ was synthesized by an usual solid state reaction and a non-conventional method of thermal decomposition of precursors. X-ray diffraction data of the monoclinic YNbO4 were used to identify the crystalline M-fergusonite phase. The symmetry of the luminescent Eu3+ site is very close to the D2 point symmetry. Spectroscopic quantities, namely, the 5D0-7F0/5D0-7F2 intensity ratio, the 5D0-7F1 transition splitting (DE0-1) and the intensity parameters Wl (l = 2, 4) were obtained from the emission spectrum at 77 K. In this sequence their values are 4.0 10-3, 103 cm-1, 18.0 10-20 cm2 and 3.2 10-20 cm2. Theoretical predictions are discussed in terms of the simple overlap model (SOM). The yttrium niobate structural data were taken as basis to obtain the spherical coordinates of the ligand oxygen atoms. The Eu-O distances being corrected in the frame of rare earth niobate series vs. atomic number. Their predicted values are 3.9 10-3, 85 cm-1, 14.9 10-20 cm2 and 3.0 10-20 cm2, assuming 0.9 as the effective charge of the ligand ions and their polarizabilities relative to the metal-ligand (M-L) distance as follows [R(Å)/ a(Å3)]: 2.443/0.6, 2.427/1.2, 2.370/2.3, 2.349/3.5.
Keywords: yttrium niobate; europium; luminescence; intensity parameters rl